Caesarean Section Delivery in India: A Comparative Assessment of Geographical Variability Using Nationally Representative Survey Factsheet Data - Tripathy, Brajaraj; jena, Ayusman; Pandey, Anuj Kumar; Mishra, Sidharth Sekhar; Mishra, Chhandasri (National Journal of Community Medicine, 2023)
Background: In line with global trends, India has witnessed a sharp rise in C-section (CS) deliveries, especially in the private sector. Methodology: Study attempts to explore change in CS delivery in India at national, regional and State/UT levels. We have used factsheet data from the most recent nationally representative survey data i.e., NFHS to examine changes in private and public healthcare facilities, and to determine a difference in rural and urban in CS deliveries. Results: The CS rate has increased from 17.2% to 21.5% in 2019-21. CS was more than twice (40.9%) amongst the private healthcare facilities during the fourth round of NFHS which has shown a considerable increase during the fifth round of NFHS (47.4%). There is equal distribution (12.8% during 2015-16 to 17.6% in 2019-21 in rural areas v/s 28.2% during 2015-16 to 32.3% in 2019-21in urban areas) of CS deliveries amongst the rural and urban areas to the total deliveries. Conclusion: Study found that with every one in five deliveries being caesarean, the figure is significantly high as per the recommended cut off by WHO. Thus, it is essential to explore factors regarding emergency or elective caesarean section and to understand if the health facilities are following the recommended protocols for performing CS deliveries.